Selective androgen receptor modulation for muscle weakness in chronic obstructive pulmonary disease: a randomised control trial. Issue 3 (25th October 2022) - Mohan, Divya; Rossiter, Harry; Watz, Henrik; Fogarty, Charles; Evans, Rachael A; Man, William; Tabberer, Maggie; Beerahee, Misba; Kumar, Subramanya; Millns, Helen; Thomas, Sebin; Tal-Singer, Ruth; et al.
Abstract : Background: Selective androgen receptor modulators (SARMs) increase muscle mass via the androgen receptor. This phase 2A trial investigated the effects of a SARM, GSK2881078, in conjunction with exercise, on leg strength in patients with chronic obstructive pulmonary disease (COPD) and impaired physical function. Methods: 47 postmenopausal women and 50 men with COPD (forced expiratory volume in 1 s 30%–65% predicted; short physical performance battery score: 3–11) were enrolled into a randomised double-blind, placebo control trial. Patients were randomised 1:1 to once daily placebo or oral GSK2881078 (females: 1.0 mg; males: 2.0 mg) for 13 weeks with a concurrent home-exercise programme, involving strength training and physical activity. Primary endpoints were change from baseline in leg strength at 90 days (one-repetition maximum; absolute (kg) and relative (% change)) and multiple safety outcomes. Secondary endpoints included lean body mass, physical function and patient-reported outcomes. Results: GSK2881078 increased leg strength in men. The difference in adjusted mean change from baseline and adjusted mean percentage change from baseline between treatment and placebo were: for women, 8.0 kg (90% CI −2.5 to 18.4) and 5.2% (90% CI −4.7 to 15.0), respectively; for men, 11.8 kg (90% CI −0.5 to 24.0) and 7.0% (90% CI 0.5 to 13.6), respectively. Lean body mass increased, but no changes in patient-reported outcomes were observed. Reversible reductions in high-density lipoprotein-cholesterol and transient elevations in hepatic transaminases were the main treatment-related safety findings. Conclusions: GSK2881078 was well tolerated and short-term treatment increased leg strength, when expressed as per cent predicted, in men with COPD more than physical training alone. Trial registration number: NCT03359473 .